Optimum predictive modelling, holistic integration and analysis of energy sources mix for power generation and sustainability in developing economies : a case of the Nigerian power system - Ayomoh, Michael (University of Pretoria, 2023)
Thesis (PhD (Industrial Systems))--University of Pretoria, 2023.